Green economy in the Western Balkans : towards a sustainable future - Renko, Sanda (Emerald Publishing Limited, 2017)
This text presents a multidisciplinary approach to the Western Balkans, addressing topics from the green image of a country, sustainable waste management, the way in which SMEs develop green entrepreneurship, sustainability in tourism and trade, green consumerism, energy efficiency, and conservation projects.